(3GdeYGdLI GdEYdGejI dCReI GdJfGaS Ydj GdWGbI h OhQgG aj ESJbQGQ efWbI GdTQb GdChSW (B/s - (3eMe``O Cf```hQ eMeO Gdge`TQj,s; (3GdSjO eMeO NGWQs; (3EjeGf eUWai eSdes (2023)
(3NdUJ GdOQGSI Edi Jbjje OhQ GdeYGdLI GdEYdGejI aj GSJbQGQ efWbI GdTQb GdChSW hPdc ef NdGd GSJYQGV JCKjQ GdHYO GdCRehi GdPi aQVJg BdjGJ GdJfGaS ddESJjdGA Ydi eUGOQ GdWGbI aj efWbI GdTQb GdChSW Ydi eNJda JHYjGJgG hefGWb JhGLOgG, hPdc aj EWGQ JMdjd fXQi dHjGf GdOhQ GdgGe GdPi dYHJg hSGFd GdEYdGe ef NdGd GdeYGdLGJ GdJj COJ Edi EfOdGY cKjQ ef GdCReGJ LYdJ ef GdefWbI eSQMkG cHjQkG dCOhGQ GdJfGaS hGdUQGY Ydi eUGOQ KQhGJ GdWGbI GdeJeKdI aj GdHJQhd hGdZGR heDNQkG GdeYGOf GdKejfI cGdPgH hGdfMGS Ydi SHjd GdeKGd dG GdMUQ eeG COi Edi JMhd GdefWbI Edi HDQ SGNfI COJ HeUjQ HYV GdOhd MjK JMhdJ Ohd eQcRjI eSJbQI Edi Ohd eaccg aGTdI hbGHdI ddJbSje WHbkG dCgOGa hEQGOI eOjQi GdCReI hGdUQGY(B.s
The study concluded to assess the role of media treatment in the stability of the Middle East by reviewing the impact of the crisis dimension imposed by the mechanisms of competition to seize energy sources in the Middle East on its various dependencies and areas of presence(3, (Bwithin the framework of a theoretical analysis to show the important role played by the media through the treatments that led to the outbreak of many crises that made the region a major theater for the roles of competition and conflict over the sources of energy wealth represented in oil and gas and recently Precious metals such as gold and copper, for example(3, (Bwhich led to the transformation of the region into hotspots that led to the fate of some countries(3, (Bas stable central states turned into disjointed, failed and divisible states according to the goals and will of the managers of the crisis and conflicts
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ (B145-150.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3EOGQI GdCReGJs; (3hSGFd GdGYdGes; (3EOGQI GdCReGJs -- (3hSGFd GdGYdGes -- (3eUGOQ GdWGbIs -- (3GdZGR GdWHjYis -- (3GdUQGYGJ GdEbdjejIs